Peran Fundamental Gembala Bagi Guru Saat Pandemik Dalam Pembelajaran Online Berbasis Karakter: Tantangan dan Sistem Pendukung - Janes Sinaga; Rudolf Weindra Sagala; Rolyana Ferinia; Stimson Hutagalung (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
The purpose of this paper is to describe the fundamental role of a pastor in a church that has a school, especially to teachers who are facing challenges and problems implementing spiritual matters in online learning. This study used a qualitative method with a descriptive approach. Data collection techniques using literature studies, using references from various library sources and journals. Interviews were conducted to corroborate the analysis and statements. As a result, the fundamental role of the pastor during the covid-19 pandemic is very crucial for teachers in the spiritual field, by providing pastoral care for teachers who are experiencing stress, praying for them specifically one by one, helping to teach students about Christian Religious Education as a whole that equipped with short worship, group prayer, and Bible reading as literacy.